STUDI PERILAKU BALOK KASTELA BENTANG PENDEK DENGAN VARIASI DIMENSI LUBANG HEKSAGONAL MENGGUNAKAN METODE ELEMEN HINGGA - Muhtarom, Ahmad (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2015)
Modification technology of castellated beams of Wide Flange beam (I WF) are now varied, starting from addition high beam variation so that moment of inertia larger than origin beam, until the hole dimension variation for the aesthetic and mechanical-electrical installations. In the castellated beams design should be noted weakening effect shear forces and buckling due to the hole modified. This study was to determine the behavior of castellated beam with hexagonal holes dimensional variations using the finite element method. The method in this research is to create a numerical model of the castellated beam 225x75x7x5 mm span of 1 meter with a hexagonal hole openings using the finite element method are verified first by the results of an experimental model. Geometry, material properties and loading both models are the same. After the numerical model results closer to experimental model results, then made 9 other castellated beam numerical models with variations in the dimensions of the hexagonal holes. The results showed that the higher and the wider hole so the larger tensile stress and compressive stress. Deflection is proportional to tensile stress and compressive stress. The smaller the ratio of the hole and holes number so the smaller the shear stress.Key Words: castellated beam, finite element method